A Study to Evaluate the Visual Outcomes and Complications of Surgical Management in Traumatic Cataract Cases - Dr Sudhanshu Shekhar; Dr Vandana Parasar; Dr Gyan Bhaskar (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Purpose: To evaluate the visual outcomes and complications of surgical management in traumatic cataract cases at a tertiary care hospital. Methods: A cross-sectional study was conducted on 66 patients with traumatic cataracts who underwent surgery. Preoperative assessment, surgical technique, postoperative visual acuity (VA), and complications were analyzed. Results: Mean age was 32.5 ± 14.2 years, with 78.8% males. Postoperatively, 62.1% achieved VA ≥6/18, while 12.1% had VA <6/60. Posterior capsule rupture (28.8%) and zonular weakness (18.2%) were common intraoperative challenges. Posterior capsular opacification (15.2%) and glaucoma (9.1%) were notable postoperative complications. Conclusion: Timely surgical intervention in traumatic cataracts yields good visual outcomes, though associated ocular injuries and complications impact prognosis. Individualized management is crucial for optimal results.